EDUKASI BANTUAN HIDUP DASAR TERHADAP PENINGKATAN PENGETAHUAN, SIKAP DAN EFIKASI DIRI BAGI PENOLONG AWAM - Cahyo, Firman Dwi (Jurnal Pengabdian Kepada Masyarakat Citra Delima, 2023)
Cardiovascular disease still dominates as the highest cause of death in the world. Cardiac arrest is a sudden loss of heart function in someone who has or has not been diagnosed with heart disease. Most cases of cardiac arrest are found around the community environment, for this reason the community has an important role in providing appropriate treatment. The success of handling cardiac arrest by ordinary people is strongly influenced by knowledge, attitudes, and self-efficacy. The purpose of this activity is to determine the effect of basic life support health education on increasing knowledge, attitudes, and self-efficacy for lay helpers. The method used in community service is divided into three stages, namely preparation, implementation, and evaluation. The implementation of this activity is carried out online through the zoom meeting application. The results of this activity showed an increase in knowledge by 52%, an increase in attitude by 8%, and an increase in the self-efficacy of lay helpers by 12%. The conclusion from this activity is that health education is very effective in increasing the knowledge, attitudes, and self-efficacy of ordinary people to provide basic life support for patients who experience cardiac arrest outside the hospital environment.